Influência dos diferentes padrões faciais nas dimensões do espaço aéreo faríngeo avaliados em tomografia computadorizada de feixe cônico - Alves, Celha Borges Costa (2018)
The pharyngeal airway space (PAS) determines vital functional processes such as swallowing and phonation. It includes nasopharynx and oropharynx and actively contributes to the development of facial morphology as a whole and the ideal occlusion. Pathological alterations that lead to PAS narrowing may cause alterations in craniofacial development due to variations in the respiratory pattern and swallowing. The relationship between PAS, severity of malocclusion, and variations in the skeletal pattern is well established. This study aimed to assess whether there is a relationship between the dimensions of PAS and the different skeletal facial patterns. A total of 207 cone beam computed tomographies (CBCTs) of patients between 20 and 40 years of age referred to orthodontic treatment were selected. These tomographic images were analyzed and divided into groups regarding anteroposterior skeletal facial pattern (APP) or maxillomandibular anteroposterior relationship (Classes I, II, and III) and vertical skeletal facial patterns (VP) dolichofacial, mesofacial, and brachyfacial. All the measures were performed by only one rater, using the software Dolphin. Statistical tests of rater calibration and of the measures obtained were conducted using the software Statistical Package for the Social Sciences (SPSS) for Windows version 24.0 at the 5% level of significance. For interrater reliability analysis, the intraclass correlation coefficient (ICC) was used. The Kruskal-Wallis test and Mann-Whitney post-test, the one-way analysis of variance (one-way ANOVA) and Tukey post-test, as well as Pearson correlation and the multivariate analysis of variance (MANOVA) of all measures of APP and VP were used. Excellent ICC results, above 0.9, were found for intrarater reliability. Statistically significant differences were found in the comparison of Class I regarding pharyngeal (p = 0.033) and oropharyngeal minimum area (p = 0.036) and pharyngeal (p = 0.024), nasopharingeal (p = 0.008), and oropharingeal anteroposterior width (p = 0.008) among mesofacial and dolichofacial patients. Mesofacial patients had significant differences in pharyngeal volume (p = 0.039), pharyngeal minimum area (p = 0.013), nasopharyngeal length (p = 0.017), and oropharyngeal length (p = 0.001) among Classes I, II, and III. For Class III, significant differences were found in nasopharyngeal (p = 0.046) and oropharyngeal length (p = 0.039) among mesofacial and dolichofacial patients. Dolichofacial patients had significant differences in nasopharingeal (p = 0.019) and oropharyngeal anteroposterior width (p = 0.012) among Classes I, II, and III. A negative correlation was found between VP and the location of minimum area of nasopharynx (p = 0.001) and oropharynx (p = 0.002), as well as between APP and nasopharingeal (p = 0.002) and oropharingeal anteroposterior width (p = 0.003). Interactions were found between APP, VP, and APP x VP. Therefore, significant differences were observed in the comparisons, correlations, and interactions between APPs and VPs and PAS dimensions.